Implementation of ICT in Higher Education as Interacting Activity Systems - Nyvang, Tom (Proceedings of the International Conference on Networked Learning, 2006)
Implementation of ICT in higher education is not a trivial process. It is however a process leading to a number of challenges and problems. The paper develops a theoretical model of the implementation of ICT in higher education based on activity theory and on a case study in a Danish university. The model suggest that implementation in itself is an activity system. The implementation activity is composed of three processes: Selection of ICT; adaptation of ICT and change of practice with ICT. Furthermore the model suggests that the implementation activity interacts with and systems development activity and an educational activity. Based on the model and case study the paper suggest a framework of challenges that must be met for an implementation to succeed.